1995
DOI: 10.1128/jb.177.22.6401-6410.1995
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a gene involved in aerial mycelium formation in Streptomyces griseus

Abstract: , S. griseus HH1, was cloned from this strain on a high-copy-number plasmid. Subcloning and nucleotide sequencing revealed that one open reading frame with 218 amino acids, named AmfC, served as a multicopy suppressor of the aerial mycelium-defective phenotype of the A-factor-deficient strain. The amfC gene did not restore A-factor or streptomycin production, indicating that amfC is involved in aerial mycelium formation independently of secondary metabolic function. Disruption of the chromosomal amfC gene in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…However, at 9 d after inoculation, M130∆amfC began to produce undecylprodigiosin, indicating that the amfC mutation delayed but did not prevent production. All of these observations suggested that amfC mutations in strain M130 influenced secondary metabolism as well as morphogenesis, in contrast to the situation in S. griseus where amfC mutations caused no detectable effects on streptomycin or A-factor production (Kudo et al, 1995).…”
Section: Phenotypes Of Amfc Mutants Derived From S Coelicolor A3(2)mentioning
confidence: 45%
See 3 more Smart Citations
“…However, at 9 d after inoculation, M130∆amfC began to produce undecylprodigiosin, indicating that the amfC mutation delayed but did not prevent production. All of these observations suggested that amfC mutations in strain M130 influenced secondary metabolism as well as morphogenesis, in contrast to the situation in S. griseus where amfC mutations caused no detectable effects on streptomycin or A-factor production (Kudo et al, 1995).…”
Section: Phenotypes Of Amfc Mutants Derived From S Coelicolor A3(2)mentioning
confidence: 45%
“…Disruption of the chromosomal amfC in wild-type S. griseus severely reduced the abundance of spores due to infrequent sporulation. Nucleotide sequences homologous to amfC are distributed in all 12 Streptomyces species tested (Kudo et al, 1995), which suggests a common role of amfC. An AmfC homologue (222 aa) in Streptomyces coelicolor A3(2) shows 60 % identity in amino acid sequence to AmfC in S. griseus.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…amfR, encoding a putative response regulator of two-component regulatory systems, is believed to act positively on the initiation of developmental processes ; its disruption abolished aerial mycelium and spore formation completely (Ueda et al, 1998). amfC cloned separately on a high-copy-number plasmid had a similar suppressive effect, and null mutation also resulted in significant loss of sporulation efficiency (Kudo et al, 1995). These results indicate that introduction of a positive regulatory gene at a high copy number may compensate for the original defects in the signal transduction system and result in the wild phenotype.…”
Section: Introductionmentioning
confidence: 51%